Dynamic modeling and experimental validation of essential oils fractionation: Application for the production of phenylpropanoids. (6th April 2020) - Arias, Julián; Casas-Orozco, Daniel; Cáceres-León, Andrés; Martínez, Jairo; Stashenko, Elena; Villa, Aída-Luz
Highlights: Fractionation of essential oils is analyzed with rigorous distillation model. Data reconciliation provided consistent initial data for dynamic distillation model. The distillation model adequately predicted the composition of cuts. Our modeling/validation methodology is transferable to other essential oils. Abstract: Batch distillation is useful in the essential oil (EO) industry to standardize and improve EO properties. Using the Lippia origanoides EO as a source of phenylpropanoids, a methodology was developed to solve and experimentally validate a batch distillation model, which described separation of EO major constituents over time. Nine EOs were distilled and their composition and distillation products were determined. Seven major constituents were used to represent the EOs and their distillation products in the mathematical analyses performed, namely, data reconciliation to modify the streams compositions in order to meet material balances, and a rigorous distillation model to describe the system dynamics. Statistical parameters ( r 2 = 0.95, M S E = 0.002 ) were calculated to compare predicted and experimental data, showing that the model can accurately predict the composition of distillation cuts. This methodology can be extended to other EOs of industrial interest to support their fractionation processes.